Extension for Community Healthcare Outcomes Based Telementoring of Physicians for Dementia–Effectiveness in India - Nair, Shruti; Sinha, Preeti; Chand, Prabhat; Sahu, Prashant; Gorthi, Naga VSS; Varghese, Mathew; Sivakumar, P. T. (Frontiers in Psychiatry, 2022)
Objective The study aimed to evaluate the effectiveness of a program based on the telementoring model [Extension for Community Healthcare Outcomes (ECHO)] for primary care physicians in diagnosing and treating patients with dementia. Method The ECHO model was adapted through 12 live sessions of 2 h every 2 weeks consisting of a didactic presentation by the expert, peer-led new case discussions, and follow-up discussions. In addition, there were 10 h of self-paced e-learning and interim assignments. The impact was examined by noting participation, session ratings, monthly clinical reports, and comparing knowledge and competency scores before and after the course. Results Among the 63 participants, 39.7% attended at least 80% of the sessions; completing the program successfully. The ratings for all sessions ranged from “good” to “excellent.” The paired sample t-test revealed a statistically significant improvement (p < 0.001) in self-rated skills and confidence in diagnosing and treating dementia with an effect size of 1.25 and 1.37, respectively. No change in the knowledge score was observed throughout the course. A considerable increase in dementia-related clinical practice was observed during four monthly summary of clinical cases. Due to the limited data of monthly reports during the COVID pandemic, no statistical analysis was attempted. Conclusion The ECHO model appears to have a positive immediate impact on the clinical ability of primary care physicians to diagnose and treat dementia. Its direct impact on patient health and at the community level should be aimed at in future studies.